Does the Experience of Discrimination Affect Health? A Cross-Sectional Study of Korean Elders. (March 2015) - Chun, Heeran; Kang, Minah; Cho, Sung-il; Jung-Choi, Kyunghee; Jang, Soong-Nang; Khang, Young-Ho
This study was conducted among 992 Koreans aged 60 to 89 to examine the effects of perceived discrimination on the health of an ethnically homogenous older population. Perceived discrimination was measured with a self-report instrument. Health outcomes included depressive symptoms, poor self-rated health, and chronic diseases. Of the elderly Koreans surveyed, 23.5% reported having experienced discrimination based on education, age, birthplace, birth order, or gender. Among women, 23.1% reported experiencing gender discrimination, compared to 0.9% among men. Men reported education and age discrimination most frequently—9.4% and 7.7%, respectively. Those who reported experiencing any discrimination were 2.19 times more likely to report depressive symptoms (95% confidence interval = 1.50-3.22) and 1.40 times more likely to report poor self-rated health (95% confidence interval = 1.02-1.93). The health effects of educational discrimination appeared most prominent. This study supports the positive associations between perceived discrimination and poorer health, particularly mental health, in later life.